Die deutsche cervelo Website
Produktbeschreibung der Rennradrahmen von "cervélo", u.a. mit folgenden Artikeln - Aerodynamic frame design- What is important: While going through the design cycle for an aerodynamic frame, we examine the different parts of the frame and their influence on its aerodynamics and mechanical properties. This will enable the reader to make his/her own decision on what he or she values in a bike frame, and hence what type of frame would be most suitable. - Aerodynamic Calculations for Cervélo Frames: The aerodynamic performance of Cervélo frames was calculated using the formulas as detailed by Jim Martin in his article. - Aerodynamics of Cycling: This article by Jim Martin, the director of sports science for Team EDS, takes a mathematical approach to calculating drag on a bicycle and rider under various conditions. Factors such as bike weight, rider position, and cycling ability are all taken into account.